Security Comparison of Messaging Protocols for Internet of Things - Jerzy KRAWIEC; Piotr GÓRNY; Maciej KIEDROWICZ (Communications of International Proceedings, 2025)
Many articles present comparative analyses of communication protocols used in the Internet of Things. However, most of them are concerned with the efficiency and functionality of these protocols, and the comparative analysis is concerned with a not very broad set of protocols. This article aims to present a pragmatic comparison of several of the most frequently used communication protocols in IoT systems when choosing a protocol regarding security. To compare the protocols in terms of security, we use the Common Vulnerabilities and Exposures (CVE) database and the Common Vulnerability Scoring System (CVSS). We present a list of security services supported by message protocols according to the criteria: Authentication, Authorization, and Confidentiality. We show the number of vulnerabilities detected in recent years regarding the protocols studied.
Keywords: Messaging protocol; IoT; Security; CVE; CVSS; Vulnerability